Physico-chemical Properties of forest Soils of Chhotaudepur Division - Karia, Jessica P.; Kiran, G. Sandhya (Indian Forester, 2004)
The study highlights the physico-chemical properties of soil under different forest classes i.e. closed Teak forest , closed mixed forest , open mixed forest , degraded forest , scrub and scrub with coppice forests , of Sajwa , Kalarani and Boriad rounds of Chotaudepur Forest Division , Vadodara District (Gujarat). This was done to have the primary information on the status of the forest soils. The physical properties of soils such as colour , texture , field capacity , pH , EC and chemical properties such as macronutrients like N , P and K and some of the micronutrients such as Z , Fe , Mn and Cu were determined for forest classes. Soils had a higher nutrient status (both macro and micro) in their topsoil. Some exceptions have been observed where the concentration of micronutrients like Mn , Fe and Cu and macronutrients like N , P and K increased in sub-surface soils. Fe and N in closed mixed forest and degraded forest , Cu and Fe in degraded and scrub forest and P and K in open mixed forest increased in sub-surface soils. The concentration of the macro- and micro- nutrients were also in good amount. Thus it shows that the soils of the forests at present are in good shape.